Media as a determinant of the sexuality of young Poles - Szymańska, Kamila; Widłak, Karolina; Pawłowski, Piotr; Kościołek, Aneta; Jakubowska, Klaudia (Journal of Education, Health and Sport, 2022)
Objective of the work: The aim of this study is to learn about the influence of the media on the sexuality of young Poles. Material and methods: The diagnostic survey method and the survey technique were used, based on the research tool which was the original questionnaire. 310 respondents, different in terms of sex, faith, place of residence and education, current family situation, aged from 16 to 21, participated in the study. Statistical analysis was carried out with the use of Exel 2019 and the SPSS Statisctics package, version 25, using the ANOVA analysis of variance and the Mann-Whitney and H Kruskal-Wallis t-tests. The data collection stage was carried out in the period from October to December 2019, via the Internet. Results and conclusions: Both men and women participating in the study view sexual, erotic and pornographic content in the mass media available to them, but women viewed pornographic content significantly less often than men. The main source of knowledge about sexuality for young Poles is the Internet. Television is relatively rare. Most of the respondents find it difficult to assess whether the media is a credible source of information on human sexuality. Most of the survey participants believe that the media content does not accelerate sexual initiation and does not affect their attitude towards sex. Believers were much less likely to support the credibility of mass media in the context of sexuality than non-believers. Key words: sexuality, sexual behavior, youth, media